The world of Leonardo, 1452-1519 - Wallace, Robert, 1919- (Time-Life library of art, 1966)
A selection of the works of Leonardo the artist, the scientist and anticipator of the modern age of technology and invention is accompanied by a text which presents and analyzes the stages of Leonardo's life and growth, including numerous quotations from his own notes and writings